Hepatic arterial infusion chemotherapy versus transarterial chemoembolization for unresectable hepatocellular carcinoma: A systematic review with meta-analysis - Si, Tengfei; Huang, Zhenlin; Khorsandi, Shirin Elizabeth; Ma, Yun; Heaton, Nigel (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Interest has revived in the use of hepatic arterial infusion chemotherapy (HAIC) for intermediate-advanced hepatocellular carcinoma (HCC) while transarterial chemoembolization (TACE) has been a longstanding loco-regional therapy. Aim: We conducted a systematic review and meta-analysis of patients with unresectable HCC treated with HAIC or TACE to look for differences in survival, adverse events, mortality and downstaging. Methods: All studies published before 29th July 2022 were identified by searching PubMed, Embase, Web of Science and Cochrane Library databases for patients with unresectable HCC and received HAIC or TACE as initial treatment. Data extracted from studies was statistically analysed using RevMan5.3 software. Results: A total of one randomized controlled trial (RCT) and 7 cohort studies (5 retrospective, 2 prospective) including 1060 (TACE group: 534, HAIC group: 526) patients were screened. Compared with the TACE group, patients who received HAIC as initial therapy had better overall survival (OS) (HR=0.53, 95%CI [0.40, 0.69]) and progression-free survival (PFS) (HR=0.54, 95%CI [0.40, 0.72]). Further subgroup analysis revealed that HAIC showed priority over TACE on prognosis outcome regardless of tumour stage, especially in patients with advanced portal vein tumour thrombus (PVTT). Utilization of port system won’t boost the efficacy of HAIC whereas using a replaced-microcatheter for each procedure could better reduce the progression disease (PD) rate (RR=0.55, 95%CI [0.40, 0.76]). The pooled RR favoured the HAIC group with regard to partial response (PR) (RR=2.87, 95%CI [2.18, 3.78]) and this was validated by both GRADE summary and trial sequential analysis. The rate of resection after treatment was higher in the HAIC group (RR=2.37, 95%CI [1.54, 3.66]), whilst no difference was found with procedure-related mortality (RR=0.56, 95%CI [0.13, 2.38]) between two groups. Compared with the traditional chemotherapy regimen (fluorouracil/leucovorin/oxaliplatin) FOLFOX-HAIC appears to be better in improving the treatment efficacy. Conclusion: Patients with unresectable HCC could potentially benefit more from HAIC rather than standard TACE treatment. A re-evaluation of HAIC as a treatment option in intermediate and advanced HCC is warranted.